2013
DOI: 10.1186/1471-2393-13-34
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review of the side effects related to the use of magnesium sulfate for pre-eclampsia and eclampsia management

Abstract: BackgroundPre-eclampsia/eclampsia is one of the most common causes of maternal and perinatal morbidity and mortality in low and middle income countries. Magnesium sulfate is the drug of choice for prevention of seizures as part of comprehensive management of the disease. Despite the compelling evidence for the effectiveness of magnesium sulfate, concern has been expressed about its safety and potential for toxicity, particularly among providers in low- and middle-income countries. The purpose of this review wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
71
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 46 publications
6
71
0
9
Order By: Relevance
“…Magnesium causes hypocalcaemia by inhibiting parathyroid hormone secretion and increases urinary excretion of calcium. 2,3 Few case reports of symptomatic hypocalcaemia secondary to magnesium sulfate were published, one of the cases was critically ill eclamptic patient treated with large dose of magnesium sulphate and she had tetany when her serum magnesium was 10 mg/ dl and her serum calcium was 6.7 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Magnesium causes hypocalcaemia by inhibiting parathyroid hormone secretion and increases urinary excretion of calcium. 2,3 Few case reports of symptomatic hypocalcaemia secondary to magnesium sulfate were published, one of the cases was critically ill eclamptic patient treated with large dose of magnesium sulphate and she had tetany when her serum magnesium was 10 mg/ dl and her serum calcium was 6.7 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…The eclampsia trial collaborative group concluded that the Magnesium sulfate reduced the hazard of frequent convulsions in eclamtiptic patient by 52% when compared with diazepam. 2 Magpic trial reported that the Preeclampsia patient had 58% lower risk of getting eclampsia than the placebo group. 2 The serum magnesium level should be between 4-7 meq/l to prevent eclampsia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations